Plant Leaves in Traditional Food Wrapping and Packaging: Culture and Identity of Melanau Ethnic in Sarawak - Zahora, Ismail; Patricia King, Jie Hung; Tunung, Robin; Mugunthan, Perumal; Adam Harris Gerten Ritay, Abdullah; Maznah, Muning (2023)
The basic role of food packaging is to protect the inner content from outside influences such as bacteria, germs or anything that could affect the taste of the food. Apart from that, packaging is also used to protect the food from damages and to pack the food. In short, the safety of the inside food and minimum environmental impact are essential. In addition, food packaging must be cost effective which satisfies requirements from consumers. The bio geographical setting of local plant species provides useful resource for traditional food wraps that has been practiced for generations. This research aims to explore the use of leaves in food wraps practiced by the Melanau ethnic in Sarawak. This study was conducted from June until December 2022 involving 400 respondents of Melanau ethnic in several villages in Mukah dan Bintulu who are knowledgeable and skilled in the traditional food preparation. Eight (8) species has been selected that are widely used by the Melanau ethnic as food wrappers. The species are Nipah leaves (Nypa fruiticans), Pandan leaves (Pandanus amaryllifolius), Nyirik leaves (Phacelophrynium maximum), Banana leaves (Musa spp.), Palas leaves (Lucasia sp.), Upih Pinang (Areca catechu), Simpoh leaves (Dillenia suffruticosa), and Mengkudu leaves (Morinda citrifolia). Most of preparation of traditional foods use the leaves of this plant especially during festivals and events causing a relatively high demand in the market. The leaves of this plant obtained from market (pasar tamu), planted in gardens, and grow naturally in certain areas. Hopefully with this documentation effort can be a reference for the entrepreneurs to meet market demand by cultivating the species in addition to preserving this species. Traditional food packaging,especially from leaves and other part of the plants are biodegradable. The traditional food is one tourism product that this country could offer. The continuing and future promotion of the cultural identity could be achieved through such preservation of the local and traditional food packaging.